Circular economy: Between theory and practice - Costel Negrei; Nicolae Istudor (Amfiteatru Economic Journal, 2018)
Misunderstanding terms like ciclicity, circularity, and nonlinearity can bring about confusion and endanger a good idea, tested by industrial ecology and widely known as "dematerialization of the economy". That is why the main the objective of the present article is to clarify the concept of "circular economy" and explain its relation with the operating laws of the economic system and the new scientific breakthroughs in systemic ecology. A secondary aim is to identify the means through which the dematerialization of the economy operates, to highlight its limits, by underlining the difference between economic growth and development and waste generation. The research methodology comprises the following stages: * Identifying the problems encountered by the concept of "circular economy" * Coming up with an analysis of the "cause-effect" relationship * Identifying the main opinions about "circular economy" expressed in the literature * Assessing to what extent the idea of "circularity" in economics has been validated. The aims of this research have led to the necessity of reaching an agreement between concepts like the economy of functionality, the adaptive economy and the specializationintegration relation.
Keywords: A10; D04; O13; Q01; Q53; 330; circular economy; entropy; dematerialization; industrial metabolism